SOSIALISASI PENGOLAHAN SAMPAH REPLACE SEBAGAI IMPLEMENTASI MATA KULIAH PENDIDIKAN LINGKUNGAN HIDUP PADA ANAK-ANAK DI SEKITAR KAMPUS UNMUH BABEL - serip, Amanda Aulia Rachman; Dian Lestari; Pipin Palinda; Lailatul Karomah; Fitri Yani; Novi Rustiana Dewi (AbdiMuh : Jurnal Pengabdian Masyarakat, 2025)
Waste problems and a lack of environmental awareness are crucial issues in the community, including those around campus. This study aims to promote the concept of "replace" (replacing single-use items with environmentally friendly alternatives) as part of the Environmental Education course for children around the UNMUH Babel campus. The research is motivated by the importance of instilling awareness and behavior in waste management from an early age in the younger generation. The community service method used is a participatory and educational approach, involving interactive lectures, audiovisual media, educational games, and hands-on practice in waste sorting. This activity targets elementary school-aged children in the campus environment. The results of the socialization show an increase in children's knowledge about the concept of "replace" and the importance of waste management. A post-activity evaluation showed that approximately 78% of participants were able to understand the concept of "replace," and 65% began to demonstrate positive behavioral changes such as bringing their own water bottles and sorting waste. However, challenges such as limited facilities and lack of family support remain obstacles. This study concludes that the socialization of the "replace" concept is effective in increasing children's environmental awareness and is a concrete implementation of the Environmental Education course.